ANALYSIS OF WELL GUSHING CONDITIONS DURING THE JOINT DEVELOPMENT OF OIL AND GAS PARTS OF OIL AND GAS CONDENSATE FIELDS (Innovative technologies, 2026)
The article presents the results of studying the conditions for well gushing in oil and gas condensate fields under development systems with priority oil extraction and gas cap gas conservation, as well as the joint operation of the oil and gas condensate parts of the deposit. The article also discusses the geological and technological factors that led to the low efficiency of oil extraction and gas cap gas conservation. The article analyzes the technological indicators of field development after switching to joint oil and gas extraction. The calculations show that well gushing is ensured by breakthrough gas from the gas cap.
Keywords: deposit; reservoir; well; method; fountain; condition; factor; parameter; oil; gas; property; gaslift